History of Katerinoslav histological school (to 100 years anniversary of histology department of Dnipropetrovsk medical academy). Part I: 1917-1962 - Marchenko, D. G.; Morozova, S. B.; Petruk, N. S.; Pototska, O. Yu.; Romanenko, L. A.; Stanishevska, N. V.; Sultanova, N. M.; Filimonova, L. A.; Khripkov, I. S.; Shevchenko, K. M.; Tverdokhlib, I. V. (Морфологія / Morphologia / Morfologìâ, 2017)
The birth of a science school is always the result of the efforts and efforts of a great scientist and celebrity. Such a scientist - the founder of the Ekaterinoslav histological school - was Professor Vladimir Porfyriyovych Karpov.